Counseling for career development - Tolbert, E. L. ([Place of publication not identifed] : Houghton Mifflin Company, 1974)
The emphasis of this book is upon practical applications supported by relevant theory and research. This book is a useful reference for those in the practicum or internship in secondary school counseling.
Chapter1. A critical need -- Chapter2. Theories of career development -- Chapter3. Understanding career development factors -- Chapter4. The information system -- Chapter5. Finding and organizing local information -- Chapter6. Decision making: individual counseling -- Chapter7. Decision making: group counseling -- Chapter8. The school guidance program -- Chapter9. Working with support personnel -- Chapter10. Placement counseling -- Chapter11. Evaluation for accountability .
Includes bibliographical references and index.
Keywords: VOCATIONAL GUIDANCE